Calcification in Atherosclerotic Plaque Vulnerability: Friend or Foe? - Shi, Xuan (Front Physiol, 2020)
Calcification is a clinical marker of atherosclerosis. This review focuses on recent findings on the association between calcification and plaque vulnerability. Calcified plaques have traditionally been regarded as stable atheromas, those causing stenosis may be more stable than non-calcified plaques. With the advances in intravascular imaging technology, the detection of the calcification and its surrounding plaque components have evolved. Microcalcifications and spotty calcifications represent an active stage of vascular calcification correlated with inflammation, whereas the degree of plaque calcification is strongly inversely related to macrophage infiltration. Asymptomatic patients have a higher content of plaque calcification than that in symptomatic patients. The effect of calcification might be biphasic. Plaque rupture has been shown to correlate positively with the number of spotty calcifications, and inversely with the number of large calcifications. There may be certain stages of calcium deposition that may be more atherogenic. Moreover, superficial calcifications are independently associated with plaque rupture and intraplaque hemorrhage, which may be due to the concentrated and asymmetrical distribution of biological stress in plaques. Conclusively, calcification of differential amounts, sizes, shapes, and positions may play differential roles in plaque homeostasis. The surrounding environments around the calcification within plaques also have impacts on plaque homeostasis. The interactive effects of these important factors of calcifications and plaques still await further study.